How to merge observational and physiological data? A case study of - Castañer, Marta; Puigarnau, Sílvia; Benítez, Raúl; Zurloni, Valentino; Camerino, Oleguer (Anales de Psicología / Annals of Psychology, 2017)
The present study analyzes individual and group heart rate responses in exercising adult women. The specific aim was to compare responses during routine workout sessions within a community exercise program with responses during a purpose-designed workout session targeting diverse motor skills. Sixty-seven adult women with a mean ± SD age of 65.1 ± 11.7 years participated in the study. Two representative sessions were analyzed: a standard workout session the women took at the local community center and an ad hoc session designed to build on a variety of motor skills and capabilities. Observational methodology was used to collect categorical data on motor skill performance during each session using the OSMOS-in context observation instrument. Continuous heart rate data were recorded for all participants during each session. A combined analysis of categorical and continuous data was undertaken using Hidden Markov Models. The results show that the session targeting a greater diversity of motor skills not only met the cardiovascular fitness recommendations of the American College of Sports Medicine, but resulted in greater individual variability and greater synchrony between participants than the routine session.